The velocity of propagation and attenuation of ultrasound in methylpyridines - LINDE, Bogumił; ŚLIWIŃSKI, Antoni (Archives of Acoustics, 1978)
The results of measurements of c and a/f^2 as functions of temperature forfive methylpyridines: β- and y-picolines and 2.4, 2.5 and 3.5 lutidines are given.